Soy isoflavone supplementation increases equol-producing capability in postmenopausal women with osteopenia - Elly Herwana (Universa Medicina, 2015)
Background Isoflavone containing soy protein has been associated with beneficial health effects. Equol, a gut bacterial metabolite of the isoflavone daidzein, has been hypothesized to be the cause of the effectiveness of isoflavones. The objective of this study was to evaluate the effect of 100 mg/day soy isoflavone supplementation for 3 months on the ability to produce equol in postmenopausal women with osteopenia.